Comparison of Fixation Strength of Mandibular Angle Fracture with Different Lengths of Miniplate and Screw Using the Champy Technique in Sheep - Pournabi, Alireza; Alijannia, Ramin; Mohammadi , Mansoureh (Regeneration, Reconstruction & Restoration (Triple R), 2020)
Introduction: This study sought to compare the fixation strength of mandibular angle fracture with 4- and 6-hole miniplates and different screw lengths using the Champy technique in sheep. Materials and Methods: This is an in vitro study in 10 sheep mandibles. The soft tissue was removed and the mandibles were sectioned at the symphysis to obtain 20 hemimandibles. An artificial fracture was induced at the mandibular angle 1 cm farther from the most distal tooth using a saw. The hemimandibles were then randomly divided into two groups (n=10) for fixation with 4- or 6-hole miniplates without a bar. Each group was then randomly divided into 2 subgroups (n=5) for using 6 or 8-mm screws. The plates were adapted over the external oblique ridge. The distance from the closest hole to the fracture line was minimally 1 mm. Next, the hemimandibles were fixed to the holding arm of the universal testing machine by self-cure acrylic resin. Compressive load was applied to an occlusal jig prepared on the occlusal surface of mandibular molars at 3 cm distance from the fracture line at a crosshead speed of 1 mm/min until fracture. Data were analyzed using SPSS version 23. Results: The mean fixation strength was not significantly different between 6-mm and 8-mm screws (P=0.243). The mean fixation strength in 6-hole miniplate group was significantly higher than that in 4-hole miniplate group (P=0.028). Conclusion: The mean fixation strength in 6-hole miniplate group was significantly higher than that in 4-hole miniplate group. It seems that 6-hole miniplates provide higher fixation strength than 4-hole miniplates, irrespective of screw length. The mean fixation strength was not significantly different between 6-mm and 8-mm screws.